Management of severe subglottic stenosis secondary to trauma: case to case comparison of resection anastomosis versus cartilage augmentation - Asha'ari, Zamzil Amin; Wan Leman, Wan Ishlah; Raja Lope Ahmad, Raja Ahmad Al'konee; Sheikh Ab. Hamid, Suzina (Malaysian Medical Associations, 2010)
We studied two similar cases of severe subglottic stenosis secondary to trauma with different treatment modalities. One had laryngotracheal reconstruction with cartilage augmentation and the other had laryngotracheal resection anastomosis. We wish to compare the two popular choices of surgery for laryngotracheal stenosis from two cases with similar nature and severity thus highlighting the complexity of managing severe subglottic stenosis in adult.